2015
DOI: 10.1111/acel.12388
|View full text |Cite
|
Sign up to set email alerts
|

Altering sphingolipid composition with aging induces contractile dysfunction of gastric smooth muscle viaKCa1.1 upregulation

Abstract: Summary KC a1.1 regulates smooth muscle contractility by modulating membrane potential, and age‐associated changes in KC a1.1 expression may contribute to the development of motility disorders of the gastrointestinal tract. Sphingolipids (SLs) are important structural components of cellular membranes whose altered composition may affect KC a1.1 expression. Thus, in this study, we examined whether altered SL composition due to aging may affect the contractility of gastric smooth muscle (GSM). We studied changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Recent evidence suggests that ceramides play a role for the aging of gastric smooth muscle. The levels of CerS2 mRNA were significantly smaller, and CerS4‐6 levels were greater in gastric smooth muscle of aged mice associated with contractile dysfunction (Choi et al, ). In skeletal muscle of mice fed with high‐fat diet, CerS1‐derived C18 ceramide promoted systemic insulin resistance (Turpin‐Nolan et al, ), indicating an impact of ceramide in skeletal muscle metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that ceramides play a role for the aging of gastric smooth muscle. The levels of CerS2 mRNA were significantly smaller, and CerS4‐6 levels were greater in gastric smooth muscle of aged mice associated with contractile dysfunction (Choi et al, ). In skeletal muscle of mice fed with high‐fat diet, CerS1‐derived C18 ceramide promoted systemic insulin resistance (Turpin‐Nolan et al, ), indicating an impact of ceramide in skeletal muscle metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…S5C). We previously reported that the CerS2 ablation‐induced alteration in the levels of CerSs and sphingolipid composition is similar to aging‐related alteration in these measurements in mice (Choi et al ., 2015b). As CerS5 was upregulated in CerS2 null mice, we examined the effects of CerS5 transfection on levels of antioxidant enzymes and K Ca 3.1 in wild‐type MAECs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then examined whether sphingosine or S1P affects K Ca 3.1 levels because sphingosine or S1P levels were increased in CerS2 null (Fig. S5C) and aged (Choi et al ., 2015b) mice. Exogenously added sphingosine (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, organization and dynamics of lipids in membranes of different subcellular structures have not been probed accurately. Interestingly, dynamics of lipid metabolism is altered during cell cycle progression in mammalian fibroblast cells (Singh et al, 2013) and aging (Choi et al, 2015). For example, about 40% increase was observed in cholesterol content in rat fibroblast cells (Singh et al, 2013) while sphingolipid levels are dysregulated during aging rats and mice (Sacket et al, 2009; Babenko and Shakhova, 2014; Mc Auley and Mooney, 2015).…”
Section: Lipid Visualization Methodsmentioning
confidence: 99%